The Development of Civics Curriculum in Indonesia: A Review of Policy and Practice - Fahruddin, Muhammad; Rahmat, Rahmat; Tanshzil, Sri Wahyuni (Journal of English Language and Education, 2026)
In Indonesia, curriculum development has been very dynamic over time. The purpose of this study is to determine the development of the Civics (PPKn) curriculum in Indonesia, from the 1947 lesson plan to the most recent, the 2020 Independent Learning curriculum. The research method used was library research. The research findings demonstrate that Indonesia has experienced highly dynamic curriculum development since the early days of independence, starting with the 1947 Lesson Plan Curriculum, the 1952 Detailed Lesson Plan Curriculum, the 1964 Education Plan Curriculum, the 1968 Curriculum, the 1975 Curriculum, the 1984 Curriculum, the 1994 Curriculum and the 1999 Curriculum Supplement, the 2004 Curriculum, the 2006 Curriculum, the 2013 Curriculum, and most recently, the 2020 Independent Learning Curriculum. Regarding Civics (PPKn), normatively, there has been quite dynamic development in nomenclature. Prior to the current nomenclature, PPKn was previously known by various nomenclatures, such as Civics, National Citizenship Education, Pancasila Moral Education (PMP), Citizenship Education, and then Pancasila and Citizenship Education (PPKn).